Maternal health behaviors during pregnancy in rural Northwestern China - Yue Ma; Yujuan Gao; Jason Li; Andrew Sun; Baozhu Wang; Jun Zhang; Sarah-Eve Dill; Alexis Medina; Scott Rozelle (BMC, 2020)
Abstract Background Maternal health during pregnancy is a key input in fetal health and child development. This study aims to systematically describe the health behaviors of pregnant women in rural China and identify which subgroups of women are more likely to engage in unhealthy behaviors during pregnancy. Methods We surveyed 1088 pregnant women in rural northwestern China on exposure to unhealthy substances, nutritional behaviors, the timing and frequency of antenatal care, and demographic characteristics. Results Pregnant women were active in seeking antenatal care and had low rates of alcohol consumption (5.1%), exposure to toxins (4.8%), and exposure to radiation (2.9%). However, tobacco exposure was widespread (40.3%), as was low dietary diversity (61.8%), unhealthy weight gain (59.7%), unhealthy pre-pregnancy BMI (29.7%), and no folic acid intake (17.1%). Maternal education is closely linked to better health behaviors, whereas experience with a previous pregnancy is not. Conclusions Tobacco exposure and unhealthy nutritional behaviors are common among pregnant women in rural northwestern China. The findings indicate that in the absence of professional health information, relying on experience of previous pregnancies alone may not help rural women avoid unhealthy maternal behaviors. Maternal health education campaigns targeting nutrition and tobacco exposure during pregnancy may improve maternal, fetal, and child health in rural China.